Ratiometric fluorescence quantitation of amoxicillin based on CDs@Eu-MOFs incorporated 3D hydrogel using smartphone-assisted portable dual mode visual sensing - Kurdistan Fakhraldin Azeez; Abdollah Salimi; Hamed Mohtasham (Sensors and Actuators Reports)
Amoxicillin (AMX) is commonly used antibiotic with a broad activity against Gram-negative and Gram-positive bacteria. Therefore, it is crucial access to an instant and real-time method for accurate and correct AMX determination. Here, we have developed a three-dimensional hydrogel modified with Europium -Metal organic frameworks (Eu-MOFs) and carbon dots (CDs) as fluorophores, which allows for ratiometric fluorescence detection of AMX. The Eu-MOFs and CDs as an AMX probe trapped in Carboxymethyl cellulose (CMC) based hydrogel. In the presence of AMX, the fluorescence intensity of CDs@Eu-MOFs, enhanced at 448 nm and decreased at 568 nm under 360 nm excitation, due to energy transfer process. Under optimal conditions, AMX determined in the linear range of 10 μM to 106.7 μM, with a detection limit of 1.17 μM in liquid state. While, in the hydrogel state, the linear range for AMX detection is from 0.3 μM to 3.07 μM, with a detection limit of 0.08 μM. So, through applying hydrogel state, assay sensitivity is increased 32-times compared with conventional using liquid state. Furthermore, the change of the fluorescence color under UV irradiation also applied for colorimetric sensing of AMX at concentration up to 106 μM with detection limit 0.63 μM using smartphone RGB color sensing software. In addition, presented assay indicates strong selectivity for AMX over other biomolecules, salts and also other antibiotics. Also, it successfully detects different quantities of AMX in water and milk samples with excellent sensitivity, precision, and reliability in both liquid and hydrogel states.